A COLLECTION OF FIBER SANDALS FROM LAST SUPPER CAVE, NEVADA, AND ITS IMPLICATIONS FOR CAVE AND ROCKSHELTER ABANDONMENT DURING THE MIDDLE HOLOCENE. Issue 2 (5th May 2017) - Ollivier, Aaron P.; Smith, Geoffrey M.; Barker, Pat
Abstract : Last Supper Cave, located in northwestern Nevada, was excavated in the 1960s and 1970s. It contained a rich record of human occupation spanning the Holocene, but many artifacts from the site, including a large basketry collection, remain unstudied. We report the results of our technological analysis and radiocarbon dating of 14 fiber sandals from Last Supper Cave, which include examples of Fort Rock, Multiple Warp, and Spiral Weft types found at other sites in the northwestern Great Basin. Radiocarbon dates on the sandals correspond well with previous dates from Last Supper Cave and suggest that it was visited episodically for over 10 millennia; however, when considered together with the growing list of dates from the site, the sandal dates suggest that Last Supper Cave saw a prolonged hiatus in occupation during the Middle Holocene—a pattern common at other sandal-bearing sites in the northwestern Great Basin. Abstract : Last Supper Cave (la Cueva de la Última Cena) está situada en el noroeste de Nevada, Estados Unidos, y fue excavada en las décadas de los 1960 y 1970. La cueva contenía un registro de artefactos cuya temporalidad abarca casi todo el Holoceno. Sin embargo, muchos artefactos procedentes del sitio, incluyendo una gran colección de cestería y canastas, aún no han sido estudiados. Aquí presentamos los resultados del fechado radiocarbónico y de nuestro análisis de métodos tecnológicos de 14 sandalias procedentes de Last Supper Cave. Estas incluyen ejemplos de urdido de fibras en los estilos Fort Rock, Multiple Warp y Spiral Weft, así como de estilos presentes en otras partes del noroeste de la Gran Cuenca. Los resultados del fechado radiocarbónico de las sandalias confirman las fechas anteriores procedentes de Last Supper Cave y sugieren que la cueva fue visitada episódicamente por más de 10 milenios. Sin embargo, cuando los datos cronológicos nuevos y anteriores se consideran en conjunto, las fechas de radiocarbono de las sandalias sugieren que hubo una pausa prolongada en la ocupación de Last Supper Cave durante el Holoceno Medio. El sitio comparte este patrón cronológico de ocupación con otras localidades en el noroeste de la Gran Cuenca donde se han encontrado sandalias.